STRATEGI KEPEMIMPINAN TRANSFORMASIONAL DAN PEMANFAATAN SUMBER DAYA MANUSIA SERTA DAMPAKNYA BAGI KINERJA PT TERMINAL PETIKEMAS SURABAYA - Mursidi, Mursidi; Widhi Yanti, Dyah Agustin; Aldiyansyah, Fikri; Alim, M.Miftahul; Tri Atmojo, Gatot Priyo; Choirudin, Muqtafi (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
The role of leadership and human resource management (HR) plays an important role in the success of an organization. Both not only influence the performance of individuals within the organization, but also shape organizational culture, direct business strategy, and ensure the organization's long-term sustainability and growth amidst ongoing changes and challenges in the business world. This research uses an exploratory and descriptive research design. The data collection techniques used were interviews, participant observation, and distributing questionnaires. The data analysis methods used include qualitative analysis and quantitative analysis. The research results show that: 1) Implementation of Transformational Leadership at PT Terminal Petikemas Surabaya plays a key role at various managerial levels. The main focus lies on important aspects such as clear vision, ability to inspire, intellectual brilliance, ability to inspire enthusiasm, and individual empowerment. 2) Utilization of Human Resources (HR) at PT Terminal Petikemas Surabaya has been effective. 3) Implementation of transformational leadership strategies and utilization of Human Resources (HR) have a significant influence on organizational performance at PT Terminal Petikemas Surabaya